Penatalaksanaan Target Temperatur Manajemen Pada Pasien Henti Jantung Dengan Irama Non-Shockable: Literature Review - Nirmana, Kurniasani; Hidayah, Nurul; Masithoh, Robiul Fitri (Jurnal Keperawatan Muhammadiyah, 2024)
Objective:  This literature review study aims to determine the management of target temperature management in cardiac arrest patients with non-shockable rhythms.Methods: The research design used is a literature review. Article search engines use Science Direct, PubMed, and Google Scholar. The keywords used include "Cardiac arrest" AND "non-shockable" AND "targeted temperature management OR TTM OR Therapeutic Hypothermia" AND "management". There were 3,282 articles. The inclusion criteria and appropriate analysis were determined using the PICOS framework approach so that 3,275 articles were issued, resulting in 7 articles being reviewed.  Results: Targeted Temperature Management, also known as therapeutic hypothermia, can improve survival and function in patients with brain damage after cardiac arrest despite optimal target temperatures. Management of target temperature management in cardiac arrest patients with non-shockable rhythms, namely: 1) The target cooling temperature used for TTM therapy is at a temperature of 32°C to 36°C for patients with early asystole or PEA. 2) Average cooling duration is at least 24 hours for TTM. Especially considering the increased side effects of prolonged cooling. 3) The cooling time used in TTM therapy is usually as soon as possible when the ROSC state of the cardiac arrest patient has returned. 4) The method usually used in the application of targeted temperature management (TTM) therapy is the placement of an intravascular catheter that allows blood circulation through an external cooling device and surface cooling by applying a large gel pad to the body containing a cold saline solution.Conclusion: Targeted Temperature Management, also known as therapeutic hypothermia, can improve survival and function in patients with brain damage after cardiac arrest despite optimal target temperatures.